2019
DOI: 10.1002/2211-5463.12738
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐7‐5p induces cell growth inhibition, cell cycle arrest and apoptosis by targeting PAK2 in non‐small cell lung cancer

Abstract: MicroRNAs (miR) are known to be critical regulators in tumor progression. miR‐7‐5p was reported to be involved in several cancers, including glioblastoma, cervical cancer, and melanoma, but its prognostic value and biological function in non‐small‐cell lung cancer (NSCLC) remain unclear. In this study, using quantitative real‐time PCR analysis, we found that miR‐7‐5p was significantly downregulated in NSCLC tissues and cell lines. Lower miR‐7‐5p expression was associated with tumor–node–metastasis stage and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…For example, Du et al (34) demonstrated that miR-335-3p expression is downregulated in NSCLC tissues compared with normal tissues. Furthermore, downregulated miR-7-5p expression has been reported in NSCLC tissues and cell lines, which exerts regulatory effects on tumor cell biological processes (35). Overexpression of miR-100 in NSCLC tissues has been demonstrated to predict the poor prognosis of this malignancy (36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Du et al (34) demonstrated that miR-335-3p expression is downregulated in NSCLC tissues compared with normal tissues. Furthermore, downregulated miR-7-5p expression has been reported in NSCLC tissues and cell lines, which exerts regulatory effects on tumor cell biological processes (35). Overexpression of miR-100 in NSCLC tissues has been demonstrated to predict the poor prognosis of this malignancy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Cells are harvested at indicated times and treated with Accumax to obtain a single cell suspension. Propidium iodide staining was completed as described (13). Cells were analyzed on a FACscan Flow Cytometer (Becton Dickensen) and cell cycle distribution determined using ModFit LT 2.0 software (Verity Software House).…”
Section: Cell Cyclementioning
confidence: 99%
“…MiR-143-3p serves as a tumor suppressor via modulating the growth, invasion and epithelial-mesenchymal transition (EMT) by regulating KH Domain Containing RNA Binding-5 (QKI-5) in esophageal squamous cell carcinoma [ 10 ]. MiRNA-7-5p inhibits cell growth, induces cell cycle arrest and cell apoptosis via modulating Paired Box 2 (PAX2) in non-small cell lung cancer (NSCLC) [ 11 ]. In ovarian cancer, miRNA-141 enhances the anoikis resistance of metastatic ovarian carcinoma cell by regulating Kruppel Like Factor 12/Sp1 Transcription Factor (KLF12/Sp1) axis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%